Peran Komunikasi dalam Membentuk Budaya Organisasi yang Inklusif di Dinas Komunikasi dan Informatika Kabupaten Sikka - Imelda Virgula Wisang; Maria Oktavia Alexandria; Maria Elisabeth Fidella; Maria Marfani; Robertus Mario Uje; Markus Valentino Putra (Universitas 45 Surabaya, 2025)
Communication plays a key role in fostering an inclusive organizational culture at the Sikka Regency Communication and Informatics Office. Effective, open, and two-way communication fosters a work environment that values diverse perspectives, backgrounds, and employee competencies. Through the implementation of structured internal communication strategies—such as transparent information dissemination, dialogue forums, and feedback mechanisms—the organization is able to strengthen collaboration and enhance a sense of belonging among all employees. The use of information technology as a communication tool also expands access and participation in decision-making processes. This inclusive work culture impacts performance, innovation, and the quality of public services. Thus, communication plays a strategic role in building an adaptive, responsive organization that is oriented toward the values of openness and diversity at the Sikka Regency Communication and Informatics Office.